Unstable Carotid Plaque as a Phenotype of Chronic Systemic Inflammation Enhances Renal Insufficiency. (16th November 2020) - Maruyama, Kunitaka; Kashiwazaki, Daina; Yamamoto, Shusuke; Hori, Emiko; Akioka, Naoki; Shibata, Takashi; Akai, Takuya; Kuwayama, Naoya; Kuroda, Satoshi
Abstract: INTRODUCTION: Chronic systemic inflammation is prevalent in patients with chronic kidney disease (CKD) and is linked to the development of cerebrovascular disease. However, although the unstable carotid plaque may also affect renal function, the mechanisms have not yet been fully elucidated. METHODS: The study included 90 patients who underwent CEA/CAS for carotid artery stenosis. Multivariate analysis was performed to determine the risk factors for CKD. Kaplan-Meier estimation was employed to evaluate the aggravation of renal function following CEA/CAS. RESULTS: Multivariate analysis revealed that contralateral carotid occlusive disease (odds ratio [OR], 4.45; 95% confidence interval [CI], 1.36-14.6), and T1 high-intensity carotid plaque (OR, 3.26; 95% CI, 1.2-8.86) were independent factors of CKD. Kaplan-Meier estimation demonstrated a higher aggravation of renal function in the T1 high-intensity group compared to those in the iso-intensity ( P  = .03). Following CEA/CAS, the time until aggravation of renal insufficiency was 12.0 § 9.4 months in the T1 high-intensity group and 24.5 § 9.6 months in the iso-intensity group ( P  = .03). CONCLUSION: This study demonstrated that contralateral carotid artery stenosis and T1 high-intensity plaques are more frequently observed in patients with CKD. T1 high- intensity carotid plaque is well linked to CKD development in future.